1999
DOI: 10.1002/(sici)1096-9896(199905)188:1<44::aid-path320>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 overexpression lacks prognostic significance in superficial urinary bladder cancer

Abstract: The biological behaviour of urinary bladder neoplasms cannot be adequately predicted by histological criteria alone. Cyclin D1 is a cell‐cycle regulating protein known to be overexpressed in a proportion of bladder carcinomas. To evaluate the prognostic significance of cyclin D1 expression and its relationship with tumour phenotype, 392 bladder carcinomas were analysed by immunohistochemistry. Clinical follow‐up information was available in 337 patients with superficial bladder tumours (stages pTa/pT1). Cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…3,4 In our study, increased expression of cyclin D1 (Ն25% positive nuclei) was more frequent in low-stage and low-grade tumors, although the differences were not significant, and was not associated with increased tumor cell proliferation, as assessed by Ki67 immunostaining. These findings are in agreement with previous studies reporting that cyclin D1 overexpression is associated with low grade and low stage 9,10,12,29 -31 and is not related with the Ki67 labeling index 12,31 nor with tumor S-phase 29 in urinary bladder cancer. A lack of association between cyclin D1 expression and tumor cell proliferation has been previously reported in breast 32 and head and neck 33 cancer.…”
Section: Predictive Power Of Combined Cyclin D1 P27 Kip1 and Ki67 Indexsupporting
confidence: 93%
See 3 more Smart Citations
“…3,4 In our study, increased expression of cyclin D1 (Ն25% positive nuclei) was more frequent in low-stage and low-grade tumors, although the differences were not significant, and was not associated with increased tumor cell proliferation, as assessed by Ki67 immunostaining. These findings are in agreement with previous studies reporting that cyclin D1 overexpression is associated with low grade and low stage 9,10,12,29 -31 and is not related with the Ki67 labeling index 12,31 nor with tumor S-phase 29 in urinary bladder cancer. A lack of association between cyclin D1 expression and tumor cell proliferation has been previously reported in breast 32 and head and neck 33 cancer.…”
Section: Predictive Power Of Combined Cyclin D1 P27 Kip1 and Ki67 Indexsupporting
confidence: 93%
“…Our results are in agreement with previous studies that also found that overexpression of cyclin D1 is associated with less aggressive disease and better survival in bladder cancer patients. 29 A lack of relationship between cyclin D1 overexpression and prognosis has been reported in superficial bladder cancer by Wagner et al, 12 who considered the presence of 10% positive cells as the cutoff to define cyclin D1 overexpressing tumors. The same authors, however, recognized that the significance of their study was hampered by the heterogeneous treatment of patients, which did not allow the exclusion that cyclin D1 status could simply affect tumor responsivity to specific treatment regimens.…”
Section: Predictive Power Of Combined Cyclin D1 P27 Kip1 and Ki67 Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…LOH analysis of sequential carcinomas from TCC patients would, therefore enable tracking of tumour suppressor gene inactivation in relation to recurrence (Bartlett et al, 1998;Wagner et al, 1999;Watters et al, 2000).…”
mentioning
confidence: 99%